The Role of Extracellular Matrix Remodeling in Skin Tumor Progression and Therapeutic Resistance - Fromme, Julia E.; Zigrino, Paola (Frontiers in Molecular Biosciences, 2022)
The extracellular matrix remodeling in the skin results from a delicate balance of synthesis and degradation of matrix components, ensuring tissue homeostasis. These processes are altered during tumor invasion and growth, generating a microenvironment that supports growth, invasion, and metastasis. Apart from the cellular component, the tumor microenvironment is rich in extracellular matrix components and bound factors that provide structure and signals to the tumor and stromal cells. The continuous remodeling in the tissue compartment sustains the developing tumor during the various phases providing matrices and proteolytic enzymes. These are produced by cancer cells and stromal fibroblasts. In addition to fostering tumor growth, the expression of specific extracellular matrix proteins and proteinases supports tumor invasion after the initial therapeutic response. Lately, the expression and structural modification of matrices were also associated with therapeutic resistance. This review will focus on the significant alterations in the extracellular matrix components and the function of metalloproteinases that influence skin cancer progression and support the acquisition of therapeutic resistance.